ESTIMATION OF THE STRENGTH OF UNDERGROUND NUCLEAR EXPLOSIONS AT TELESEISMIC DISTANCES ON THE BASIS OF SHORT-PERIOD P WAVES - Kedrov O.K. (My University, 1988)
This paper discusses a method of evaluating explosion strength from short-period waves at the teleseismic distance range. It is well known that the seismic method gives extremely accurate estimates of the strength of a nuclear explosion if data on the structural properties of the rock in which it occurs exist. But if there is no such information, then estimates based on the seismic method may be in error by a factor of 2 or more. But even a knowledge of the rock type does not give a full idea of the properties of the medium. In developing a method of estimating strength and an energy scale, Soviet recordings of United States underground nuclear explosions in Nevada and on Amchitka Island were used. Analysis of many recordings of underground explosions in Nevada revealed that the dynamic properties of a train of P waves correlate with the conditions at the source. Additional aspects of the subject are discussed.